IMPROVING ELEVENTH-GRADE STUDENTS’ SPEAKING SKILLS THROUGH DEBATE ACTIVITIES DESIGNED WITH ROLE-PLAY - Aprillia Putri; Yunik Susanti; Rika Riwayatiningsih (JURNAL KOULUTUS, 2026)
Speaking is an important skill in learning English. However, some students find it difficult to express their ideas and communicate their messages confidently. The present study focused on the effect of role-play discussion exercises on students’ speaking skills. This study was quantitative pre-experimental one group pre-test post-test design with 22 eleventh grade students of SMAN 6 Kediri. Data were collected through interactive speaking assessments and analysed with descriptive statistics and a paired-sample t-test. The results showed that the mean score was increased from 64.36 to 78.18 at significance level 0.001 (p < 0.05). The results indicated that the role-play debate activities significantly enhanced the students’ speaking skills and helped them to communicate meaningfully in EFL classrooms.